Flexible power weighting distribution for three‐phase parallel inverters with networked control. Issue 7 (1st July 2015) - Ma, Hao; Lin, Zhao; Lin, Liaoyuan; Zhang, Yao; Wang, Xiaorui
Abstract : In this study, networked control scheme applied in dq 0 coordinate for three‐phase parallel inverters of distributed generation units is presented to achieve flexible current weighting distribution. Firstly, the output impedance based on generalised state space averaging method with the consideration of dead‐time effect is investigated in dq 0 coordinate and proved to be inductive for fundamental components in dq 0 coordinate. Therefore the weighted output current distribution can be realised conveniently with networked control applied in dq 0 coordinate without the additional circuit or virtual impedance. Besides, for the sake of flexibility and autonomy of a parallel inverters system, the power proportional coefficients of different inverters can be changed automatically. In the end, power weighting coefficients in networked control are optimised by means of functional analysis. The experimental results demonstrate the effectiveness of a networked control scheme applied in dq 0 coordinate on the flexible power weighting distribution for parallel inverters.